Media Preneurship Study for The Dynamics Journalism in Indonesia - Briandana, Rizki; Haris, Abdul; Marta, Rustono Farady; Chinmi, Maichel; Aliagan, Isiaka Zubair (Universitas Semarang, 2022)
Introduction: YouTube, is one of the most popular forms of new media platforms in Indonesia. The freedom of the people who can act as creators or spectators is a special attraction for the community, moreover the availability of many choices of content has increasingly made YouTube the mainstay of the best-selling entertainment media. The rise of television journalists using social media, especially YouTube, has made an appeal for studies to be carried out to analyze the dynamics which enables them to utilize their professional competencies as a mediapreneur.Methods: This study applied a qualitative approach. The method used was the case study approach with in-depth interview and observation as the data collection techniques. The informants for the interview were the television journalist in Jakarta. There were eight television journalists who were used as informants for this study.Findings: This study found that the presence of new technology in journalistic work practices has eroded professional values. This research reveals the recognition of the erosion of professional values due to the impact of new media, coupled with the interests of entrepreneurial journalists who act as content creators for their own economic interests. Therefore, one way that is able to perpetuate existence is the strengthening and sharpness of in-depth and intact journalism.Originality: This study has become a novelty since no previous studies in Indonesia which analyze the role of journalists as professionals and also as content creators in mediaprenership efforts in the digital era.